PENGEMBANGAN SISTEM INFORMASI PENJUALAN BUKU BUCERDAS: PENGEMBANGAN SISTEM INFORMASI PENJUALAN BUKU BUCERDAS - SAYUTI, AKHMAD (Jurnal Teknik Ibnu Sina (JT-IBSI), 2023)
A good information system will really support every activity, especially in cyberspace. Books that previously could only be ordered or purchased in bookstores can now be done in cyberspace (the internet), on the internet. Customers can search for books in the book catalog based on book categories, and can search in the menu bar. The book ordering system here describes the activity of ordering books on the internet network which provides easy facilities for book consumers in searching for information about the book they are looking for. This project aims to design and create a book ordering information system that makes it easy to order books on the website and also easy to view the required book information. The benefit of this system is that it makes it easier for book consumers to no longer have to bother looking for the books they need by traveling long distances to buy books. The system creation method includes system analysis in the form of a FlowChart, system design in the form of a Context Diagram, DFD, ERD. The results of the system are applied in the form of web design using the PHP programming language and database management using MySQl with the Apache web server.